2010
DOI: 10.1057/jit.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Political Discussion Networks: A Model for the Analysis of Online Deliberation

Abstract: This paper shows that online political discussion networks are, on average, wider and deeper than the networks generated by other types of discussions: they engage a larger number of participants and cascade through more levels of nested comments. Using data collected from the Slashdot forum, this paper reconstructs the discussion threads as hierarchical networks and proposes a model for their comparison and classification. In addition to the substantive topic of discussion, which corresponds to the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 27 publications
0
81
0
3
Order By: Relevance
“…Morever, the last three metrics have been suggested to quantify the level of deliberation in online discussion threads [13]. This approach is based on the Madisonian conceptualization of deliberation as the conjugation of two dimensions: representation and argumentation [1].…”
Section: Structural Metrics Of Discussion Cascadesmentioning
confidence: 99%
“…Morever, the last three metrics have been suggested to quantify the level of deliberation in online discussion threads [13]. This approach is based on the Madisonian conceptualization of deliberation as the conjugation of two dimensions: representation and argumentation [1].…”
Section: Structural Metrics Of Discussion Cascadesmentioning
confidence: 99%
“…This activity can lead to heated discourse. Recent research on political discussions within non-political groups has also found that political discussions tend to be more active than others (Gonzalez-Bailon, Kaltenbrunner, & Banchs, 2010).…”
Section: Political Engagement On the Internetmentioning
confidence: 99%
“…We also build on prior work that utilizes social network analysis methods to understand comment streams. Previous research on the networks and discussion participation within online discussion forums has focused on comments streams in USENET forums and Slashdot (Gonzalez-Bailon, S., Kaltenbrunner, A., and Banchs, R. E. 2010, Fiore, LeeTiernan, Smith 2002, Gomez, Kaltenbrunner, Lopez, 2008. These studies have relied on the construction of networks and analysis of participation based on explicit connections made through replies to other previous posts.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant research and practice is heavily influenced by deliberative democracy theory, which is based on the assumption that "public, plural discussions offer a superior form of collective decision making" [1]. Consequently, preferences should not just be aggregated (as in voting) but should be rather "revised in the light of a preceding debate" [2].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, preferences should not just be aggregated (as in voting) but should be rather "revised in the light of a preceding debate" [2]. Despite its promises however, scholars soon concluded that putting the theory in practice is a challenging task [1,3].…”
Section: Introductionmentioning
confidence: 99%